Analisis Pengelolaan Keuangan Startup Dalam Mencapai Keberlanjutan Bisnis - Jua Anugrah Jaya Laoli (CV. SINAR HOWUHOWU, 2026)
This study examines the strategic dilemma faced by startups in choosing between aggressive market share growth and achieving short-term profitability. In the digital economy era of 2026, a shift in investor sentiment from